2018
DOI: 10.1158/1538-7445.am2018-lb-273
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-273: A head-to-head comparison of the properties of five clinical PARP inhibitors identifies new insights that can explain both the observed clinical efficacy and safety profiles

Abstract: Four poly(ADP-ribose) polymerase (PARP) inhibitors have now presented phase 3 monotherapy data showing compelling benefit of targeting tumours enriched with DNA damage response (DDR) pathway deficiencies, including BRCA gene mutations. Indirect treatment comparisons using the published clinical data from these late stage trials suggest similar levels of monotherapy efficacy are observed in spite of reported differences in PARP trapping potency. However, there is greater diversity in the observed safety profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…For example, a recent study by Leo and colleagues comparing all aforementioned PARP inhibitors, apart from pamiparib, showed that the cytotoxic potential of each of the five PARP inhibitors differs between HRR-deficient (HRD) and HRR-proficient isogenic cell lines, whereby olaparib showed the most HRD-specific sensitivity, and talazoparib was the most agnostic to HRR status with regard to its cytotoxicity. Veliparib displayed the least efficacy in both the HRD and HRR-proficient lines (24).…”
Section: Preclinical Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, a recent study by Leo and colleagues comparing all aforementioned PARP inhibitors, apart from pamiparib, showed that the cytotoxic potential of each of the five PARP inhibitors differs between HRR-deficient (HRD) and HRR-proficient isogenic cell lines, whereby olaparib showed the most HRD-specific sensitivity, and talazoparib was the most agnostic to HRR status with regard to its cytotoxicity. Veliparib displayed the least efficacy in both the HRD and HRR-proficient lines (24).…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…1; refs. 23,24). In addition, sequential tumor and/or liquid biopsies in PARP inhibitor-treated preclinical models and patients are giving researchers a better understanding of the underlying mechanisms of sensitivity and resistance to this class of drugs, potentially paving the way forward for the development of functional biomarkers for rational patient selection.…”
Section: Are All Parp Inhibitors Created Equally?mentioning
confidence: 99%
See 3 more Smart Citations